Overtraining from a sports psychiatry perspective - Schorb, A.; Niebauer, J.; Aichhorn, W.; Schiepek, G.; Scherr, J.; Claussen, M. C. (Deutsche Zeitschrift für Sportmedizin, 2021)
Overtraining is characterized by a mismatch between exerted strain and exercise tolerance. Overtraining is generally not sufficiently feared nor is enough attention paid to its prevention. As a result, the first warning signals and symptoms are often either perceived too late or there is a delay in the correct interpretation of signs. This often leads to negative consequences over months, which, in turn, can lead to more frequent injuries as well as Depression.